Fabrication of a highly efficient polymer electrolyte membrane by embedding nanofibrous metal oxide in cell components. (29th November 2019) - Wang, Guanzhong; Ji, Deqiang; Wu, Hongjun
Abstract: In this work, a high-performance polymer electrolyte membrane based on sulfonated polyether ether ketone (SPEEK) loaded with zirconium oxide nanofibres (ZrN) was fabricated. ZrN with an average diameter of 182 nm were prepared by pyrolysing electrospun polyacrylonitrile fibres embedded with a zirconium precursor. The weight percentage of added ZrN and the relevant performance of the hybrid membrane (e.g., proton conductivity, methanol permeability and fuel cell performance) were experimentally determined and verified. It was found that the SPEEK-ZrN hybrid membrane exhibited sufficient proton conductivity (25.9 mS cm −1 ), low methanol permeability (1.64 × 10 −7  cm 2  s −1 ) and superior selectivity (15.8 × 10 4  S s cm −3 ) at room temperature. Compared to a pure SPEEK membrane, the SPEEK-ZrNT-1.5 membrane showed 1.3 and 1.7 times higher current density and power density, respectively. Graphical abstract: Zirconium oxide nanofibres (ZrN) were fabricated by annealing polymer fibre mats containing a zirconium precursor. A series of SPEEK-ZrN hybrid membranes containing different contents of ZrN were prepared. The better dispersion of inorganic nanofibres could provide more long-range conducting pathways within the membrane, thus the improved DMFC properties of SPEEK-ZrN hybrid membranes were obtained. Image 1 Highlights: The zirconium oxide nanofibers (ZrN) were successfully fabricated by calcining electrospun nanofibers. Effects of calcination process on properties of ZrN were evaluated. Embedding ZrN within SPEEK improved proton conductivity and methanol resistance at low loadings.